2006
DOI: 10.1002/pd.1597
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-echogenic colon: a prenatal sign of cystinuria?

Abstract: We suggest the term 'hyper-echogenic colon' to describe a hyperechoic foetal colonic content with no other intestinal abnormality. This is a rare pattern, which to our knowledge, has never been correlated with a specific pathology. The accidental observation of a cystine kidney stone in an infant who presented with this sign during the prenatal period made it possible to diagnose this disease retrospectively in two other children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 6 publications
0
27
0
3
Order By: Relevance
“…Lorsque le diagnostic échographique de cystinurie est évoqué, l'IRM n'est pas indispensable. Elle est utile pour rechercher des malformations digestives associées [9].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Lorsque le diagnostic échographique de cystinurie est évoqué, l'IRM n'est pas indispensable. Elle est utile pour rechercher des malformations digestives associées [9].…”
Section: Discussionunclassified
“…Après la découverte d'un côlon hyperéchogène, il est nécessaire de réaliser une enquête génétique, une amniocentèse (caryotype, recherche de mucoviscidose), une analyse chromatographique du liquide amniotique et des sérologies maternelles [9].…”
Section: Discussionunclassified
“…This abnormality was unexplained until recently. In 2006, Brasseur-Daudruy et al [6] reported a hyper-echogenic colon in the third trimester of pregnancy in a girl who had lithiasis at 14 months of age. Cystinuria was subsequently diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…In four of the six fetal hyper-echogenic colons (samples were not available for two), cystinuria was confirmed after birth. Brasseur-Daudruy et al [6] found cystine in the meconium in one new-born. These researchers hypothesized that this might have been a consequence of the fetus absorbing amniotic fluid containing a large quantity of cystine, which would be excreted by the fetal kidneys in cases of cystinuria.…”
Section: Discussionmentioning
confidence: 99%
“…La situation la plus fréquente est dominée par la gestion du risque lié à la découverte d'un grêle hyperéchogène [13][14][15]. Le bilan initial, orienté par l'anamnèse, repose sur la biologie (bilan infectieux, caryotype, recherche de mutations pour la mucoviscidose) plus que sur l'imagerie.…”
Section: Diagnostic D'une Pathologie Du Tube Digestif Foetalunclassified